Tinjauan Konstitusional PraRatifikasi Perjanjian Internasional: Studi Perbandingan Sistem Hukum Indonesia dan Hungaria - yuvita Mardiana; Nuzula Sari; Yusuf Adiwibowo (Jurnal Hukum Lex Generalis, 2026)
The increasing involvement of states in international treaties creates tensions between international obligations and constitutional supremacy. Indonesia does not yet have a constitutional pre-ratification review mechanism, putting it at risk of both domestic unconstitutionality and international liability. In contrast, Hungary implements preventive review based on the 2011 Hungarian Constitution (Alaptörvény), supported by the 2011 CLI Law on the Constitutional Court, reflecting a fundamentally different constitutional design. Using normative legal research through comparative and conceptual approaches, this study finds that the existing ex post review model in Indonesia creates systemic vulnerabilities not present in Hungary's ex ante system. As a novelty, this study offers a three-tier adaptation model encompassing constitutional amendments, legislative revisions and progressive judicial interpretation to integrate constitutional pre-ratification review into the Indonesian legal system. The proposed model positions Pancasila as the staatsfundamentalnorm in the constitutional review of international treaties, an element not present in the Hungarian constitutional framework.